Long-term safety and effectiveness of canakinumab therapy in patients with cryopyrin-associated periodic syndrome: results from the β-Confident Registry - Walker, Ulrich A (RMD Open, 2021)
OBJECTIVE: To report the long-term safety and effectiveness of canakinumab, a fully human anti-interleukin 1β monoclonal antibody, in patients with cryopyrin-associated periodic syndromes (CAPS), including familial cold autoinflammatory syndrome (FCAS), Muckle-Wells syndrome (MWS) and neonatal-onset multisystem inflammatory disease (NOMID), in a real-world setting. METHODS: From December 2009 to December 2015, the β-Confident Registry prospectively enrolled patients with CAPS and non-CAPS conditions who received canakinumab per routine care and were prospectively followed for up to 6 years. The registry protocol did not mandate specific visits or procedures; however, all observed adverse events (AEs) and serious adverse events (SAEs) had to be recorded. Canakinumab effectiveness was evaluated by Physician’s Global Assessment (PGA). RESULTS: Of 288 patients enrolled, 3 were excluded due to missing informed consent. Among the remaining 285 patients, 243 (85.3%) were patients with CAPS and 42 (14.7%) had atypical CAPS (6.3%) or other conditions (8.4%). The median age was 26.6 years. Based on PGA, 58 of 123 (47.2%) patients with CAPS had no disease activity at 48 months, and 65 of 123 (52.8%) experienced mild/moderate disease activity at 48 months. Among CAPS phenotypes, AE incidence rates per 100 patient-years were lowest for FCAS (73.1; 95% CI 60.3 to 87.8) compared with those with MWS (105.0; 95% CI 97.2 to 113.2) or NOMID (104.6; 95% CI 86.6 to 125.2). One hundred twenty-eight SAEs were reported in 68 patients with CAPS (incidence rate/100 patient-years, 14.0; 95% CI 11.6 to 16.6). One death (metastatic rectal adenocarcinoma in a patient with MWS) was reported. CONCLUSIONS: The response to canakinumab was sustained for up to 6 years. Canakinumab demonstrated a favourable safety profile over long-term treatment in patients with CAPS. TRIAL REGISTRATION NUMBER: NCT01213641.